Current state of personal data protection in electronic voting: demand on legislature’s Bill - Lubis, Muharman; Kartiwi, Mira; Zulhuda, Sonny (Institute of Electrical and Electronics Engineers Inc. (IEEE), 2017)
The strongest benefit has been offered for the implementation of electronic voting related to cost and time reduction. Therefore, recent publicity concerning the reliability, security and privacy issue of various e-voting systems has increased public scrutiny of the machines themselves as well as the election process as a whole. In the greater scale, it could reduce public confidence to entrust the adoption of e-voting system to augment participation rate, to improve the quality of voting and to aid the political right effectively and efficiently. This paper aims to provide general analysis of typical legal issues and its demand for personal data protection based on demographic data such as gender, age, occupation, electoral participation, education, earnings and legal literacy. By understanding the perception of voters in viewing current electoral regulation are essential to provide some insights and suggestion for better improvement, either through drafting or enforcing legislation. This study investigates the tendency of people in demanding the legislative to cater electronic voting.